Analysis of Block of cell proliferation 1 (BOP1) activity in strawberry and Arabidopsis. (April 2016) - Carvalho, Sofia D.; Chatterjee, Mithu; Coleman, Lauren; Clancy, Maureen A.; Folta, Kevin M.
Highlights: First characterization of BOP1 in planta . BOP1 is essential for plant viability. Plant BOP1 has a role in pre-rRNA processing and cell division as in other eukaryotes. Abstract: Block of cell proliferation (BOP) proteins are conserved among eukaryotes, and studies in mammals and yeast have described their role in ribosome biogenesis and cell cycle regulation. A BOP1 orthologue was identified in plants, and loss-of-function analyses in tobacco cells confirmed similar activities. This report characterizes a role for BOP1 activity in planta . Two transgenic plant species were used: the diploid strawberry ( Fragaria vesca ) and Arabidopsis thaliana . FvBOP1 silencing showed changes in pre-rRNA processing, and demonstrated FvBOP1's role in growth and physiology throughout different stages of plant development. In the strawberry, repression of FvBOP1 activity decreased plant fitness prior to flowering, followed by plant death after the reproductive transition, indicating that BOP1 activity is required for transition back to vegetative growth after flowering. A T-DNA null allele of the AtBOP1 gene is lethal, and a 50% decrease in transcript accumulation is sufficient to cause severe developmental defects linked to defective cell division. The conserved protein BOP1 is essential for viability. Lower transcript levels result in defects in rRNA processing and developmental abnormalities that are consistent with its predicted role in ribosome biogenesis.